THE AUTHORITY OF POLICE INVESTIGATORS IN REVEALING CORRUPTION (STUDY AT THE BINJAI RESORT POLICE) - Herio Simanjuntak; Mustamam Mustamam; Indra Gunawan Purba (Jurnal Ilmiah METADATA, 2026)
Police investigators have the authority to uncover corruption crimes, in accordance with Law Number 8 of 1981 concerning the Criminal Procedure Code (KUHAP) and other laws and regulations. This authority includes investigations and investigations, as well as other actions necessary in legal proceedings. Based on the results of the study, it is known that the obstacles for police investigators in uncovering corruption crimes are both internal and external aspects. Some of the internal obstacles include limited human resources, suboptimal legal understanding, and lack of coordination between agencies. Meanwhile, external barriers include political pressure, lack of public support, and obstacles in the collection of evidence.